Immobilized inclusion bodies of recombinant cold-adaptive lipase from Antarctic Pseudomonas sp. as catalysts - Bello, Muhammad Nura; Sabri, Suriana; Mohd Yahaya, Normi; Mohd Shariff, Fairolniza; Mohamad Ali, Mohd Shukuri (Springer Science and Business Media Deutschland GmbH, 2025)
Abstract: Immobilization of lipase has been receiving attention for a long time; this is because of the need for robust catalysts by industries. Numerous literature has reported improvements in the properties of immobilized lipase in terms of stability when exposed to extreme conditions of temperature, pH, and organic solvents commonly encountered in most industrial settings. However, some microbial lipases that have the potential to catalyze significant reactions do occur in the form of inclusion bodies when expressed in Escherichia coli. This research aimed to immobilize catalytically active inclusion bodies (CatIBs) of LipAMS8 lipase onto Seplite LX120 as the adsorption material. Scanning electron microscopy and Fourier infrared spectroscopy were used to ascertain the immobilization. Immobilized CatIBs have an optimum temperature of 20 °C and pH of 9.0. They exhibit high stability to broad temperatures, pH levels, and organic solvents, with excellent storage stability and reusability, retaining 50% of their residual activity after ten cycles. They demonstrated excellent activity in the transesterification of waste cooking oil with methanol, in which 2% of the immobilized CatIBs produced up to 98% biodiesel in a ratio of 1:9 at 25 °C for 7 h at 200 rpm. LipAMS8 CatIBs immobilization improved their stability and capability to produce biodiesel at lower temperatures. Key points: •Catalytically active inclusion bodies from recombinant AMS8 lipase occurring naturally were successfully immobilized onto seplite LX120. Morphological and structural analyses using SEM and FITR confirmed the immobilization. •Characterization revealed the immobilized LipAMS8 CatIBs to maintain the residual activity of up to 50% at a broad temperature (10–80 °C) and pH (4–12). •Interactions with metal ions and various organic solvents manifest their stability. Transesterification reaction with methanol using palm cooking oil to produce biodiesel at 25 °C which revealed their synthetic capacity.